Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Employee engagement Karyawan PTPN VII Kedaton Bandar Lampung - Hendri Dunan; Ayu Arisma (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to investigate the influence of leadership on work behavior and employee participation in PT PTPN VII Kedaton Bandar Lampung. The research subject consisted of 73 of his collaborators, who were also the sample for this study. Data was collected by questionnaire and analysis was performed using multiple regression. Analysis showed that leadership has a large impact on the employees involved (tcount = 10,799 > ttable = 1,658). In addition, employee engagement has a positive impact on employee performance (tcount = 6,140 > ttable = 1,658). The F-test shows the effect of culture and work environment on employees (Fcount = 50.397 > Ftable = 3.85). Furthermore, the t-test shows a significant effect of changes in work environment on employee work engagement (t count = 6.140 > t table = 1.658). Overall, the study concludes that there is not only an impact of culture and work environment on employees of PT PTPN VII Bandar Lampung, but also an impact between the leadership and performance of the employees involved.